(untitled) (ARTEKS : Jurnal Teknik Arsitektur, 2021)
Biophilic design is a well-known design philosophy based on human-nature relationships. However, it has not been explored extensively in the Malaysian context and most of the previous studies were based on plants which were not suitable for tropical climate. This paper analyses the application of biophilic design and the usage of local edible and medicinal plants in Baba-Nyonya heritage shophouses’ courtyards in George Town UNESCO World Heritage Site, Penang, Malaysia. The aim of this research is to enhance the human quality of life through biophilic design with local knowledge application in the urban setting. Qualitative method strategies were applied to collect the data: photographic survey, plant inventory and building observation. Three heritage shophouses that had been adaptively reused into contemporary cafes were selected for this study. Significant results showed that Biophilic Design Pattern under the ‘visual connection with nature (P1)’ has been achieved through the application of edible and medicinal plants. Unfortunately, the local knowledge for applying edible and medicinal plants for achieving biophilic design compliance is weak. In the future, a further study is needed to identify the species of local edible and medicinal plants which can be applied in the Baba-Nyonya heritage shophouses courtyards.